Ludicrum: escenarios de juego (2020)
The game in the city seems to have been reduced to the area of ??a court, but how do we understand the game without first asking the children? Gambling is a task of urban equity, which should be focused on one of the most vulnerable populations, children, however, how do we find safe play spaces within the city? How could we design diverse spaces where children can play? It is necessary to recondition the playful-urban strategies for the development of the game. LUDICRUM seeks to resolve these concerns by generating versatile spaces for play, using a simple frame structure that allows the enclosures within the complex to be dynamic and flexible; This is how the space at an architectural level can be of the necessary dimensions according to the activities to be developed by children and young people. The core of the project lies in the semi-basements, which are called Las Jugueterías, it is these who act as storage for toys...